Endogenous Firm Heterogeneity, ICT and R&D Incentives - Daniel Cequera; Gordon J. Klein (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
Firm heterogeneity explains the productivity driven selection mechanism that determines aggregate productivity growth within industries. This paper empirically demonstrates that ICT has a robust impact on firm heterogeneity only when ICT is used intensively and jointly with specific ICT applications. ICT induced heterogeneity is shown to have a positive impact on the decision to invest in R&D personnel.
Keywords: L25; D21; O32; 330; Firm Heterogeneity; Information and Communication Technologies; Creative Destruction; R&D Incentives; Firm Level Data; Computergestütztes Verfahren; Informationstechnik; Innovationsdiffusion; Produktivität; Wettbewerbsstrategie; Schumpeterismus; Industrielle Forschung; Ökonomischer Anreiz; Theorie